(untitled) (GUB Journal of Science and Engineering, 2018)
A rigorous theoretical investigation has been made on the linear propagation of electrostatic perturbation modes of degenerate pressure driven modified nucleus-acoustic (DPDMNA) ‘waves in a degenerate quantum plasma (DQP) system. It contains cold inertia-less degenerate electron species (DES), cold inertial non-degenerate light nucleus species (LNS) and stationary heavy nucleus species (HNS) which maintains the quasi-neutrality condition at equilibrium only. The mass density of the cold LNS provides the inertia and the cold inertia-less cold LNS provides the inertia and the cold inertia-less DES gives rise to the restoring force. The reductive perturbation method has been used for the study of nonlinear propagation of the DPDMNA waves. The basic features of linear waves are supervised in a theoretical manner. It has been observed that the phase speed of DPDMNA waves changes with the change of charge density of the stationary HNS for both non-relativistic and ultra-relativistic DES; The NA waves with their dispersion properties which are consequential in various astrophysical and laboratory plasmas, have been broadly considered. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 20-23